Lead exposure in firearms instructors of the Italian State Police / Esposizione a piombo negli istruttori di tiro della Polizia di Stato italiana - Di Lorenzo, L.; Borraccia, V.; Corfiati et al., M. (La Medicina del Lavoro, 2010)
Background: Several studies evaluated exposure to lead in relatively small groups of firearms instructors and shooters, mainly operating at indoor ranges. Objective: To assess the levels of lead exposure in a large sample of firearms instructors of the Italian State Police (SP) operating at either indoor or outdoor ranges. Methods: A cross-sectional study was conducted in firearms instructors working in indoor (No. 188) and outdoor (No. 188) ranges compared with 170 food plant workers. The personal and work characteristics and  current blood lead (Pb-B) levels were evaluated. The concentrations of environmental lead (Pb-E) were measured using personal samplers in 6 indoor and 6 outdoor firing ranges. Results: The Pb-B levels in the two groups of firearms instructors were well below the ACGIH BEI, but significantly higher than in food plant workers. In the entire study sample the Pb-B level was seen to be influenced by age and job group. An excess risk of having Pb-B >100 μg/l was found in indoor range instructors and in those with greater job seniority. Pb-E 100 μg/l negli istruttori indoor e in quelli con più di 10 anni di anzianità di mansione. In tutti i poligoni esaminati sono stati misurati livelli di Pb-E